Analysis of mitochondrial haemoglobin in Parkinson's disease brain - Shephard, Freya; Greville-Heygate, Oliver; Liddell, Susan; Emes, Richard D.; Chakrabarti, Lisa (Elsevier, 2016)
Mitochondrial dysfunction is an early feature of neurodegeneration. We have shown there are mitochondrial haemoglobin changes with age and neurodegeneration. We hypothesised that altered physiological processes are associated with recruitment and localisation of haemoglobin to these organelles. To confirm a dynamic localisation of haemoglobin we exposed Drosophila melanogaster to cyclical hypoxia with recovery. With a single cycle of hypoxia and recovery we found a relative accumulation of haemoglobin in the mitochondria compared with the cytosol. An additional cycle of hypoxia and recovery led to a significant increase of mitochondrial haemoglobin (p b 0.05). We quantified ratios of human mitochondrial haemoglobin in 30 Parkinson's and matched control human post-mortem brains. Relative mitochondrial/cytosolic quantities of haemoglobin were obtained for the cortical region, substantia nigra and cerebellum. In age matched postmortem brain mitochondrial haemoglobin ratios change, decreasing with disease duration in female cerebellum samples (n = 7). The change is less discernible in male cerebellum (n = 18). In cerebellar mitochondria, haemoglobin localisation in males with long disease duration shifts from the intermembrane space to the outer membrane of the organelle. These new data illustrate dynamic localisation of mitochondrial haemoglobin within the cell. Mitochondrial haemoglobin should be considered in the context of gender differences characterised in Parkinson's disease. It has been postulated that cerebellar circuitry may be activated to play a protective role in individuals with Parkinson's. The changing localisation of intracellular haemoglobin in response to hypoxia presents a novel pathway to delineate the role of the cerebellum in Parkinson's disease.